Clara Schumann Studies - Davies, Joe (Cambridge New York, NY Cambridge University Press, 2021)
"Since the 1980s, when she re-emerged from the peripheries into a more central position in music studies, Clara Schumann (1819-1896) has exerted an enduring fascination over the scholarly and popular imagination. Revisionist biographies, the uncovering of primary sources (diaries, letters, memorabilia), and filmic and literary depictions of Schumann have all brought into sharper focus the details and reception of her life, while simultaneously drawing attention to how much there is still to learn about her creativity. This book brings together a team of leading scholars to reappraise Clara Schumann in three particular respects: first, by delving deeper into her social and musical contexts; secondly, by offering fresh analytical perspectives on her songs and instrumental music; and thirdly, by reconsidering her legacy as a pianist and teacher"--
Introduction. Clara Schumann in the Musicological Imagination / Joe Davies -- Clara and Robert Schumann's Circles in Dresden : 'I take the liberty to request from you an invitation [...] to your musical matinee' / Anja Bunzel -- Disillusionment and Patriotism: Clara and Robert Schumann in the Wake of the 1848-1849 Revolutions / Susan Youens -- Softened, Smudged, Erased : Punctuation and Continuity in Clara Schumann's Lieder / Stephen Rodgers -- A Way with Words : Expressive Declamation in Clara Schumann's Songs / Harald Krebs -- Clara Schumann and the Nineteenth-Century Piano Concerto / Joe Davies -- Clara Schumann and Bach / Susan Wollenberg -- Formal Innovation and Virtuosity in Clara Schumann's Piano Trio in G minor, Op. 17 / Nicole Grimes -- Contextualizing Clara Schumann's Romanzen / Katharina Uhde & R. Larry Todd -- The Young Prophetess in Performance / Amanda Lalonde -- Clara Schumann's Compositional and Concertizing Strategies, and Robert Schumann's Piano Sets / Alexander Stefaniak -- Clara - Robert's Posthumous Androgyne / Roe-Min Kok -- Clara Schumann, 'Clara Schumann', and the American Press / Jonathan Kregor -- Clara Schumann's Legacy as a Teacher / Natasha Loges.
Includes bibliographical references and index.
Keywords: Schumann, Clara -- 1819-1896; Bach, Johann Sebastian -- 1685-1750; 19th Century (1801-1900); Composer; Biography; Song; Concerto; Chamber music; Music education; Piano; Germany